THE MODE OF THE HALYCH BORDERLAND IN THE WORK OF JOSEPH ROTH - Khorob, Stepan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article explores the features of the epic thinking of the prominent Austrian writer, a native of Galicia (Brody), Josef Roth. Actually, this was the purpose of the study. It is proven that this was very clearly manifested in the works of the “Galician borderland”, which the author used with different functionality (starting with the topos and ending with national-ethnic modes). In such a broad aspect of studying the originality of the ideological and aesthetic consciousness of a foreign artist of the word, the emphasis is placed on how in the novels, short stories, stories and reports of Josef Roth, Galicia is understood and recreated as an object and subject of his artistic thinking. For this purpose, the article applies the appropriate research methods: philological, hermeneutic, cultural-historical. As a result of studying the problem posed on the material of Josef Roth's prose works about the "Galician borderland", their originality and organicity in the general work of the classic of Austrian literature have been proven. This, in fact, is the novelty of the study.